Proteomics reveals the effects of sustained weight loss on the human plasma proteome. Issue 12 (22nd December 2016) - Geyer, Philipp E; Wewer Albrechtsen, Nicolai J; Tyanova, Stefka; Grassl, Niklas; Iepsen, Eva W; Lundgren, Julie; Madsbad, Sten; Holst, Jens J; Torekov, Signe S; Mann, Matthias
Abstract: Sustained weight loss is a preferred intervention in a wide range of metabolic conditions, but the effects on an individual's health state remain ill‐defined. Here, we investigate the plasma proteomes of a cohort of 43 obese individuals that had undergone 8 weeks of 12% body weight loss followed by a year of weight maintenance. Using mass spectrometry‐based plasma proteome profiling, we measured 1, 294 plasma proteomes. Longitudinal monitoring of the cohort revealed individual‐specific protein levels with wide‐ranging effects of losing weight on the plasma proteome reflected in 93 significantly affected proteins. The adipocyte‐secreted SERPINF1 and apolipoprotein APOF1 were most significantly regulated with fold changes of −16% and +37%, respectively ( P  < 10 −13 ), and the entire apolipoprotein family showed characteristic differential regulation. Clinical laboratory parameters are reflected in the plasma proteome, and eight plasma proteins correlated better with insulin resistance than the known marker adiponectin. Nearly all study participants benefited from weight loss regarding a ten‐protein inflammation panel defined from the proteomics data. We conclude that plasma proteome profiling broadly evaluates and monitors intervention in metabolic diseases. Synopsis: Longitudinal plasma proteome profiling of 52 obese individuals during weight loss and maintenance reveals 93 significantly altered proteins, including panels correlating with inflammation and insulin resistance. 1, 294 plasma proteomes are measured by single‐run mass spectrometry. 93 significantly changed plasma proteins are detected upon weight loss. Global changes in the apolipoprotein family reflect metabolic risk. A ten‐protein low‐grade inflammation and an insulin resistance panel are defined. Abstract : Longitudinal plasma proteome profiling of 52 obese individuals during weight loss and maintenance reveals 93 significantly altered proteins, including panels correlating with inflammation and insulin resistance.